Urgensi Visum Et Repertum dalam Pembuktian Tindak Pidana Pembunuhan - Tri Bowo Hersandy Febrianto; Handar Subhandi Bakhtiar (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Visum et repertum is a statement made by a forensic doctor at the written request of an investigator for the purposes of proof in a criminal act, one of which is the crime of murder. Visum et repertum is used as a substitute for the corpse of a crime victim who cannot possibly be presented in court, so it plays a very important role in revealing the identity, time and cause of death.  This research aims to explain the urgency of the post mortem et repertum in proving the crime of murder so that the resolution of the case becomes clear and clear. The approach method used is normative juridical which is an approach carried out based on the main legal material by examining theories, concepts, legal principles and statutory regulations and by using one of the Marsinah cases as a benchmark for the urgency of post mortem. et repert. The results of the research show that post mortem et repertum has an important role in proving the crime of murder, namely that it can help provide clues to the identity, time and cause of death of the murder victim.